Formation of Students’ Logical Thinking within the Multicultural Educational Society - Khalabuzar, Oksana; Kondratieva, Olena; Chykil, Maria; Nikishyna, Tetiana (Journal of History Culture and Art Research, 2019)
The article focuses on the analysis of the aspects of training of future teachers within the modern multicultural society. The modern process of education is characterized by an interacting process of globalization. The multicultural orientation is reflected in the educational standards of teachers’ preparation. These processes cause reform of the education system for Bachelors and Masters of pedagogical specialties. A modern future teacher should be able to create a dialogue with all the participants of the society and human intercultural relationships within the educational process. The article identifies pedagogical conditions for the effectiveness of the formation of students’ culture of logical thinking. The solutions of the stated goal were provided by a set of methods: systemic interviewing, non-standard tasks, and interactive educational technologies, oriented on the forming of logical skills, testing, questioning, statistical method. The authors of the article offer a number of recommendations for more-effective ways of training future teachers. Special emphasize should be made on the formation of a positive motivational component which is oriented on the realization of personality’s potential abilities and gives the opportunity to form and to develop logical thinking. The article contains the strategy of forming a positive attitude and positive motivational atmosphere within the educational process, the method of non-standard educational work (case study which presents the way of formation multicultural thought, brain-storms, discussions, on-line conferences, mind-maps, etc). The methods of charting, through which students were able to discuss the term or the notion, analyzing positive and negative features, were used for the formation of a culture of logical thinking. Diagnostics of the quality level of students’ logical skills by questioning to determine the level of formation of abilities to analyze, to compare, to determine the main idea, to generalize and to make correct conclusions. The strategy, oriented on the creation of a dynamic atmosphere, on the mobilization of the students’ logical thinking is proposed.